2017
DOI: 10.9721/kjfst.2017.49.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dry aging on physicochemical properties of beef cattle loins

Abstract: This study investigated the quality change in dry aged beef cattle loins (temperature: 3±1, lative humidity: 75±5%, period: 14 days), compared to non-aged beef cattle loins (control). The water content of dry aged loins was lower than that of the control (p<0.001). The fat content, protein content, pH value, and redness in dry aged loins were higher than in the control. Moreover, dry aging significantly improved the water holding capacity and cooking yield of beef cattle loin (p<0.001). The shear force of dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…During the same aging period, the yellowness difference between aging methods was as follows: the EFR groups showed significantly lower values than the CR groups at wk 1 (p<0.05) but significantly higher values in all subsequent aging weeks (p<0.05). In line with our results, several previous studies have reported a decrease in lightness and an increase in redness and yellowness with a prolonged aging period upon beef loin aging (Choe and Kim, 2017;Wicklund et al, 2005). Park et al (2019) aged pork loin under EFR and reported that lightness decreased with increasing aging period, while yellowness increased until wk 2 of aging and then decreased, a result similar to that of this study.…”
Section: Colorsupporting
confidence: 93%
See 3 more Smart Citations
“…During the same aging period, the yellowness difference between aging methods was as follows: the EFR groups showed significantly lower values than the CR groups at wk 1 (p<0.05) but significantly higher values in all subsequent aging weeks (p<0.05). In line with our results, several previous studies have reported a decrease in lightness and an increase in redness and yellowness with a prolonged aging period upon beef loin aging (Choe and Kim, 2017;Wicklund et al, 2005). Park et al (2019) aged pork loin under EFR and reported that lightness decreased with increasing aging period, while yellowness increased until wk 2 of aging and then decreased, a result similar to that of this study.…”
Section: Colorsupporting
confidence: 93%
“…Campbell et al (2001) reported that the group with a long aging period (21 days) showed lower shear force than the groups with relatively short aging periods (7 days and 14 days). Choe and Kim (2017) reported on beef loin that the 14-day dry-aged group had a lower shear force than the non-aged beef. Smith et al (2008) reported that the shear force of beef loin (short loin) tended to decrease upon aging.…”
Section: Waner-bratzler Shear Force (Wbsf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Dashdorij et al [10] reported that dry-aged meat with a unique flavor was highly preferred by consumers. Choe and Kim [11] reported that this aging technique was being used to add market value to low-grade cattle beef.…”
Section: Introductionmentioning
confidence: 99%